FENOMENA KEMISKINAN DAN PERDAGANGAN PASAR GELAP DI PERBATASAN INDONESIA–TIMOR LESTE - Petrus Welland Nomleni, Anton; D Kameo, Daniel (KRITIS, 2025)
ABSTRACT This study aims to analyze the economic opportunities and challenges faced by families living along the Indonesia–Democratic Republic of Timor-Leste (RDTL) border, particularly at points of cross-border smuggling and black-market trade. The research employs a qualitative case study approach, with data collected through in-depth interviews involving informants familiar with the economic and social dynamics of the border region. The findings reveal that the persistence of illegal trade reflects the government’s inability to ensure adequate welfare and economic access for border communities. Restrictive regulations have limited local economic activity, prompting many families to engage in clandestine trade as a survival strategy. This study contributes theoretically by interpreting informal border economies as both adaptive mechanisms and acts of resistance against unfavorable state policies. The findings offer valuable insights for developing more inclusive and context-sensitive economic policies in border areas.